Functionalized Separators Boosting Electrochemical Performances for Lithium Batteries - Zixin Fan; Xiaoyu Chen; Jingjing Shi; Hui Nie; Xiaoming Zhang; Xingping Zhou; Xiaolin Xie; Zhigang Xue (Nano-Micro Letters)
Highlights The commonly used modification methods for separator of lithium batteries are summarized, which include surface coating, in situ modification and grafting modification. The adhesion of coating materials with the separators and wettability of the modified separators prepared from the three methods are compared. The challenges and future directions of separator modification are provided.